The composition and unrevealed immune role of non-RLR DExD/H box RNA helicases in fish - Shan Nan Chen; Xue Yun Peng; Pin Nie (Comparative Immunology Reports)
The large superfamily of DExD/H box RNA helicases are involved in various life processes, such as RNA metabolism, transcriptional regulation, translation, tumorigenesis, cell cycle, and viral infection, and RIG-like receptors (RLRs) in the superfamily have been confirmed with crucial roles in viral infection by recognizing viral RNA. In this review, non-RLR DExD/H box RNA helicases were possibly summarized in relation with their composition and antiviral immune responses in teleost, with at least 52 genes in the helicase subfamily. Compared with mammals, most DExD/H box RNA helicases in teleost are conservatively present, but some are present in a fish-specific gene duplication manner or have been lost in evolution, which may imply the obvious compositional difference in fish. The comparison in innate immune roles of mammalian and teleost DExD/H box RNA helicases indicated that DDX3a, DDX3b, DHX9, DDX41, DDX43 are functional positively in anti-viral/bacterial immunity in fish, while DDX1, DDX3a, DDX5, DDX19, DDX23 negatively in the immunity. In the future, the composition, possible immune recognition, signalling and interaction with other immune pathways, as well as other biological functions are all of significant importance for research, which may contribute to the development of disease prevention and control strategies in aquaculture.